STRESS MANAGEMENT IN EDUCATIONAL UNITS - Br Manjorang, Rasfanzely; Tarigan, Natalia Widya Pasca; Ginting, Roy Dedi Ansarika; Siahaan, Melisa Anjelina; Siwi C. W, Theresia Dwi (English Language Teaching Prima Journal (ELT), 2022)
This research is aimed to find out the aspects causing stress among the schools staff and how the principal of the school manage it. This research was conducted at Telkom 2 Vocational schools. Descriptive qualitative research design was used in order to collect the data. From the analysis of the data, it was found some facts, they are teachers' work-related stress was caused by their roles and responsibilities as teachers, as well as by their nature, behavior, and limitations as students. Non-work-related sources of stress at work include working hours that are viewed as excessively long by informants and a lack of family time. Complaints at the time of teaching that are felt in the form of dizziness, headaches, and tiredness are symptoms of work stress. Mind and body, daydreaming, and sighing looks Individual approaches, such as sharing a story or chatting with colleagues, time management by allowing children to express themselves, and organizational approaches, such as improving internal teacher communication organization through relationships with superiors, colleagues, and students, and providing support social support from the school through annual walks, are all methods of stress management.